Gestión de procesos de negocios en función de una arquitectura orientada a servicios - Arias Chaves, Michael (San José: Editorial Universidad de Costa Rica, 2010)
This article describes the process of implementing a business process management supported by a service-oriented architecture from a business perspective. Also, it is to suggest how you can do to effectively balance the use of BPM and SOA as an entity differentiator for modern companies that drive the achievement of agile and flexible processes in their businesses.